2017
DOI: 10.1016/j.jval.2017.08.1388
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Drug Prescription Patterns and their Impact on Outcome of Blood Pressure in Ethiopia:A Hospital-Based Observational Study

Abstract: Objectives: PARADIGM-HF, a phase III trial conducted in patients with heart failure and reduced ejection fraction (HFrEF), showed that sacubitril/valsartan, a first-inclass angiotensin receptor-neprilysin inhibitor, provided incremental cardiovascular and overall survival benefit compared to enalapril. This analysis aimed to quantify the number of potential all-cause deaths that could be avoided with optimal usage of sacubitril/valsartan for the treatment of HFrEF in Costa Rica. MethOds: Data from Instituto Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The finding was similar to the studies conducted at Gondar University Hospital and Zewditu Memorial Hospital, Addis Ababa, Ethiopia, and it might be due to comparable health care professionals, health care service, and medication availability. 22,25 The prevalence of appropriate use of antihypertensive medications was 44.2% in this study. It was lower than studies conducted in South Indian (65%) and South Africa (51.9%).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The finding was similar to the studies conducted at Gondar University Hospital and Zewditu Memorial Hospital, Addis Ababa, Ethiopia, and it might be due to comparable health care professionals, health care service, and medication availability. 22,25 The prevalence of appropriate use of antihypertensive medications was 44.2% in this study. It was lower than studies conducted in South Indian (65%) and South Africa (51.9%).…”
Section: Discussionmentioning
confidence: 53%
“… 24 In contrast, according to a study conducted in Gondar, Ethiopia, loose combination pills therapy produced better BP control than monotherapy. 25 Another study conducted in Jimma, Ethiopia, showed that the number of antihypertensive medications prescribed was not associated with BP control. 26 Furthermore, studies on guidelines adherence and rate of BP control have been limited by cross-sectional study design; therefore, this prospective cohort study was conducted to assess clinicians’ adherence to hypertension treatment guidelines and BP control among ambulatory adult hypertensive patients at Jimma University Medical Center (JUMC).…”
Section: Introductionmentioning
confidence: 99%
“…We performed a sensitivity analysis of the prevalence of uncontrolled HTN by applying a random-effects model. Each excluded study showed a slight difference in pooled estimate of prevalence of uncontrolled HTN, the highest and lowest estimates being 53.1% (95% CI, 45.3%–60.8%) ( 35 ) and 49.99% (95% CI, 41.9%–57.9%) ( 34 ) when the respective studies were omitted.…”
Section: Resultsmentioning
confidence: 96%
“…The AHA/ACC guidelines ( 33 , 34 ), JNC-8 ( 22 , 24 , 25 , 28 , 30 32 , 35 45 ), and JNC-7 ( 23 , 27 , 29 , 46 , 47 ) were used as assessment tools for 2, 19, and 5 studies, respectively. Eight studies were conducted in the Amhara region ( 22 , 26 , 32 , 33 , 35 , 36 , 45 , 46 ), nine in Oromia ( 24 , 25 , 28 31 , 37 , 43 , 47 ), one in the Southern Nations, Nationalities, and Peoples' Region (SNNPR) ( 34 ), four in Addis Ababa ( 39 , 40 , 42 , 44 ), and four in Tigray ( 23 , 27 , 38 , 41 ). In this meta-analysis 9,046 study participants were involved and 4,415 of them were found to have uncontrolled HTN.…”
Section: Resultsmentioning
confidence: 99%